A Literature Review of the Psychosocial Development of Preschool Children - Delima; Tisnawati; Herwati (proceedinginternational, 2023)
The development of each child is different both in talents, interests, creativity, emotional maturity, personality, physical and social health. The purpose of this study was to determine how the psychosocial development of pre-school age children from various literatures. This study uses a Literature Review research design with a traditional type of review using the PICO strategy. Articles were searched using the electronic database Science Direct, Research Gate, NCBI Pubmed, Semantic Scholar, Wiley Online Library, Google Scholar, and Clinical Key for Nursing. The results of this study, found as many as 6589 journal articles and as many as 7 journal articles that the author can analyze further based on the PRISMA selection flow. Based on the research, it can be concluded that the psychosocial development of preschool-aged children is that children like to fantasize and be creative, children have the initiative in playing with tools at home, children who like to play with peers will easily be separated from their parents, children understand better what is right and what is wrong. wrong, children learn to string words and sentences, children recognize various colors, children help with simple homework, children recognize their gender, learn new skills through games. Nurses are expected to be able to carry out appropriate stimulation according to the stage of psychosocial development of pre-school children.